IT Department Demand Governance in Health Care: Reflections on a Case Series - Leu, Michael G.; Ize-Ludlow, Diego; Landman, Adam B.; Abbaszadegan, Hamed; Monsen, Craig B. (ACI Open, 2022)
Background Little is written on how best to structure IT governance in health care organizations. Governance is challenging because these groups may contain administrators, clinicians, and staff in addition to IT employees; projects may be complex and have significant impact on the teams that provide patient care.Methods Peer organizations in health care were purposefully selected and C-suite executives were interviewed about their IT governance. Notes taken from these conversations were analyzed for guiding principles.Results We interviewed leaders from five peer organizations. Consensus principles included: (1) minimize unwarranted variation; (2) evolve governance with the organization but independently of projects; (3) govern all clinical applications; (4) be flexible with intake, yet clear on decision-making; (5) have a tiered approach to governance; and (6) be multidisciplinary. Emerging principles included: (1) assign an IT business relationship manager to each high priority initiative, (2) have a clear escalation path to a small number of decision-makers, (3) include analytics to inform governance, (4) leverage Informatics expertise, and (5) use structured tools to streamline the process.Conclusion While IT governance is very different across distinct health care organizations, there are some general principles that many share.
Keywords: governance; health information technology; case series